2012
DOI: 10.1242/jcs.099374
|View full text |Cite
|
Sign up to set email alerts
|

Splice-variants of the P2X7 receptor reveal differential agonist-dependence and functional coupling with pannexin-1

Abstract: SummaryP2X7 receptors function as ATP-gated cation channels but also interact with other proteins as part of a larger signalling complex to mediate a variety of downstream responses that are dependent upon the cell type in which they are expressed. Receptor-mediated membrane permeabilization to large molecules precedes the induction of cell death, but remains poorly understood. The mechanisms that underlie differential sensitivity to NAD are also unknown. By studying alternative variants of the mouse P2X7 rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 64 publications
1
64
0
Order By: Relevance
“…In this study, T cells were found to preferentially express P2X7K, whereas macrophages preferentially express P2X7A. This may account for differences in P2X7 signaling between these cell types in rodents (Hong 648 et al, 2009;Xu et al, 2012) and suggests that P2X7 variants may mediate the differential sensitivity of macrophages and lymphocytes to NAD. However, the relative contribution of different P2X7 splice variants on NAD-mediated P2X7 activation in other cell types, such as astrocytes, has not been investigated.…”
Section: B P2x7 Splice Isoformsmentioning
confidence: 53%
“…In this study, T cells were found to preferentially express P2X7K, whereas macrophages preferentially express P2X7A. This may account for differences in P2X7 signaling between these cell types in rodents (Hong 648 et al, 2009;Xu et al, 2012) and suggests that P2X7 variants may mediate the differential sensitivity of macrophages and lymphocytes to NAD. However, the relative contribution of different P2X7 splice variants on NAD-mediated P2X7 activation in other cell types, such as astrocytes, has not been investigated.…”
Section: B P2x7 Splice Isoformsmentioning
confidence: 53%
“…These results suggest that, the mechanism of P2X7 receptor activation by ART1-mediated ribosylation does not occur in human immune cells as reported in murine models (Aswad & Dennert, 2006;Hong et al, 2009). This conclusion is supported by results observed with patch-clamp assays in which NAD did not activate the P2X7 receptor and behaved like a partial agonist of the P2X7 receptor (Xu et al, 2012). CD39+ Treg cells may be less sensitive to ATP or NAD because they exhibited a lower level of P2X7 and ART1 expression; however the results with CD39-Treg cells, which expressed higher levels of P2X7 when compared with CD39+ Treg cells, do not support this latter hypothesis.…”
Section: Discussionmentioning
confidence: 80%
“…Both types of resting CD4 ϩ T-lymphocytes failed to respond to either 100 M BzATP or 1 mM ATP; at these concentrations, both agonists fully activate P2X7kRs (57,89). Likewise, activated conventional CD4 ϩ T cells did not respond to either agonist with inward current.…”
Section: Resultsmentioning
confidence: 92%